The Bitter Pill of Name-Brand Drugs - Gorin, Moti (The Hastings Center report, 2015)
Imagine a drug—let's call it Curebitt—that is safe, cheap, and very effective: take a pill once a day and you will be healthier. Curebitt's taste is so unpleasant, so bitter, however, that a significant proportion of patients cannot bring themselves to ingest the pill regularly. Now suppose that after some time, another drug, Curesweet, hits the market. This drug is clinically equivalent to Curebitt and costs the same, but it is much more palatable, so adherence rates for it are significantly higher than for Curebitt. Should physicians continue prescribing Curebitt, now that Curesweet is available? No, prescribing the bitter pill puts patients at a greater risk of nonadherence and ultimately results in reduced clinical benefit for a significant proportion of patients, whereas prescribing Curesweet benefits more patients and increases the probability that any given patient's health will improve. The Curebitt versus Curesweet scenario draws our attention to how a physician can fail her patients by prescribing drugs with lower adherence rates when equivalent drugs with higher adherence rates are available. What does this fictional case tell us about the real world? A lot. We know that adherence rates vary with out-of-pocket costs. Name-brand drugs carry higher out-of-pocket costs than their generic counterparts; as a result, when name-brand drugs are prescribed rather than their generic counterparts, fewer patients receive health benefits. If prescribing Curebitt is unethical, then so is prescribing the name-brand drug.